2014
DOI: 10.1111/wbm.12051
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐tuning of a mowing regime, a method for the management of the invasive plant, Ambrosia artemisiifolia, at different population densities

Abstract: Common ragweed (Ambrosia artemisiifolia) is an invasive annual plant with highly allergenic pollen. Its spread in introduced and native ranges often occurs on roadsides, where it builds stable and rapidly growing populations. The most sustainable way of controlling the population size of this species is to prevent seed production in order to deplete the soil seed bank. Populations on roadsides are submitted to regular mowing management, which can even exacerbate the situation by inducing resprouting after cutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Regrowth of ragweed after mowing is well-documented (Barbour and Meade 1981, Bohren et al 2005, Bohren et al 2008, Meiss et al 2008, Karrer et al 2011, Patracchini et al 2011, Simard and Benoit 2011, Tokarska-Guzik et al 2011) and varies with season (Milakovic et al 2014b). Timing and frequency of cutting has specific influences on the seed production of ragweed (Simard andBenoit 2011, Milakovic et al 2014a).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Regrowth of ragweed after mowing is well-documented (Barbour and Meade 1981, Bohren et al 2005, Bohren et al 2008, Meiss et al 2008, Karrer et al 2011, Patracchini et al 2011, Simard and Benoit 2011, Tokarska-Guzik et al 2011) and varies with season (Milakovic et al 2014b). Timing and frequency of cutting has specific influences on the seed production of ragweed (Simard andBenoit 2011, Milakovic et al 2014a).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, aim of any sustainable long-term control of common ragweed should be a reduction of the soil seed bank in established populations. Milakovic et al (2014a and2014b) and Bohren et al (2008) found that seed production per plant could be influenced by carefully timed mowing. This study's goal is to test the effect of different cutting regimes applied for three years (Milakovic et al 2014a) on the quantity and quality of the ragweed soil seed bank.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, we do not, unfortunately, have field data on how mowing affects recruitment, sizes of new plants and plant survival of our species and hence, we did not include such effects in our models. Plant survival is unlikely to be directly affected much by mowing as our species has large capacity for re-growth, forming new lateral shoots when the main stem is cut (Bohren et al 2008;Kazinczi et al 2008;Milakovic et al 2014a). Such resprouting was even observed in 75-100% of plants cut two or three times (Milakovic et al 2014a;Patracchini et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Plant survival is unlikely to be directly affected much by mowing as our species has large capacity for re-growth, forming new lateral shoots when the main stem is cut (Bohren et al 2008;Kazinczi et al 2008;Milakovic et al 2014a). Such resprouting was even observed in 75-100% of plants cut two or three times (Milakovic et al 2014a;Patracchini et al 2011). If mowing removes or weakens competitors, recruit-ment, survival and the size of new A. artemisiifolia plants may be promoted (Bazzaz 1979).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation